CLARIS-La Plata Basin: Regional hydroclimate variability, uncertainties and climate change scenarios - Boulanger, Jean Philippe (2016)
The CLARIS-LPB project, funded from 2008 to 2012 by the 7th Framework Programme of the European Commission, aimed at projecting regional climate change impacts in the La Plata Basin (LPB) in southeastern South America focusing on the periods 2010-2040 and 2070-2100. Such a coordinated projection of regional climate change scenarios was key in successfully designing adaptation strategies for land-use, agriculture, rural development, hydro - power production, river transportation, water resources and wetland ecosystems. Topics covered in this special include characteristics of climate variability over the region, together with trends, extreme events and uncertainties for modelled regional climate projections.